Pengaruh Paket Pendidikan Kesehatan Siaga Risiko Stunting (Skoring) Terhadap Pengetahuan dan Sikap Ibu Mencegah Stunting di Wilayah Kerja Puskesmas Bandarharjo - Sindi Afrinza Dewi; Apriliani Yulianti Wuriningsih; Hernandia Distinarista (Lembaga Pengembangan Kinerja Dosen, 2025)
Stunting is a serious health issue that significantly impacts children's growth and development, increasing the risk of diseases, brain development disorders, as well as motor and cognitive delays. This study aims to analyze the effectiveness of the Stunting Risk Awareness Health Education Package (Skoring) in improving mothers' knowledge and attitudes toward stunting prevention at the Bandarharjo Public Health Center. This research employs a quantitative method with a quasi-experimental design, involving 53 respondents selected through purposive sampling. The intervention was carried out by providing health education related to stunting to mothers with toddlers. The findings indicate a significant increase in mothers' knowledge and attitudes after receiving the education. The average knowledge score increased to 16.00, while 84.9% of respondents demonstrated a positive attitude toward stunting prevention. Statistical analysis also confirmed a significant effect with a p-value of 0.000, indicating that the health education provided played a crucial role in enhancing mothers' awareness and knowledge about stunting. Based on these findings, it can be concluded that health education is effective in improving mothers' understanding and awareness of stunting prevention. Therefore, healthcare professionals are encouraged to be more proactive in providing education to the community in order to reduce stunting rates and ensure optimal child growth and development.